PENINGKATAN KINERJA BERBASIS PADA KOMITMEN ORGANISASI DENGAN STRATEGI DAN INOVASI - Kristianto, Djoko (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2007)
Abstract Researcher trying to do research of social area specially related to make-up of organizational effectifity, make-up of organizational effectifity become important because representing one of the target of organization. Existence of resource human being in organization represents one of the important aspect especially with the organizational effectifity. Important human resource in make-up of organizational effectifity because of invesment in conducted human resource by much organization is by dozens and this matter designate that human resource represent important shares. More and many good organization of conciousness or unconscious stay in the tight emulation atmosfir. Hence no doubt again that situation in this time more and more to require high flexibility because of speed the happening of change. In face of emulation which more and more to tighten and more and more to have nuance of is make-up of the performa, organization find its improvement by way of improving effectifity from organization. Keywords: performance, organizational, support strategy, innovation